2016
DOI: 10.15446/dyna.v83n196.50402
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic behavior of yellow pitahaya treated with 1-MCP

Abstract: Foods may have both solid and liquid properties, and are described as viscoelastic products. Knowledge on such viscoelastic features is very useful for quality control and/or food stability. The purpose of this work was to evaluate the effect of the application of 1-MCP on the viscoelastic properties of minimally processed yellow pitahaya during refrigeration storage, by using a stress relaxation test. Viscoelastic parameters were determined through Generalized Maxwell and Peleg's rheologic models. Both rheolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…(Herak et al., 2015). Whereas other authors reported that Peleg model represents better experimental data for pitahaya (Torres‐Valenzuela et al., 2016) and cherries (Moghimi et al., 2011). Differences depend on the type of fruit and ripening stage; the experimental procedure; different instruments used; and parameter conditions, such as test speed, test time, and force (Alirezaei et al., 2013).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…(Herak et al., 2015). Whereas other authors reported that Peleg model represents better experimental data for pitahaya (Torres‐Valenzuela et al., 2016) and cherries (Moghimi et al., 2011). Differences depend on the type of fruit and ripening stage; the experimental procedure; different instruments used; and parameter conditions, such as test speed, test time, and force (Alirezaei et al., 2013).…”
Section: Resultsmentioning
confidence: 94%
“…Published studies reported that Maxwell model represents better experimental data in different food matrixes, such as date fruits (Alirezaei et al, 2013;Hassan et al, 2005), kashar cheese (Karaman et al, 2016), papaya, mango, banana (Torres et al, 2012), and seeds of Jatropha curcas L. (Herak et al, 2015). Whereas other authors reported that Peleg model represents better experimental data for pitahaya (Torres-Valenzuela et al, 2016) and cherries (Moghimi et al, 2011). Differences depend on the type of fruit and ripening stage; the experimental procedure; different instruments used; and parameter conditions, such as test speed, test time, and force (Alirezaei et al, 2013).…”
Section: Elastic and Viscous Elementsmentioning
confidence: 99%
See 1 more Smart Citation